Perlindungan Hukum Konsumen Dihubungkan dengan Undang-Undang Nomor 4 Tahun 2023 Tentang Pengembangan dan Penguatan Sektor Keuangan (Studi Putusan Nomor: 15/Pdt.Sus-Bpsk/2023/Pn.Grt) - Fauzi, Muhamad Jiia; Guntara, Deny; Abas, Muhamad (Universitas Ekasakti, 2023)
There are several things that buyers should pay attention to when making purchases online through E-Commerce. The approach taken in this research is a normative legal study. Legal exploratory standardization, written examination or truth study, is that this research is normative juridical research. In the mediation carried out by BPSK on May 29 2023, the process from start to finish was carried out without the presence of the applicant, so that the applicant had no good faith at all. However, the applicant filed an objection to the Garut District Court on the basis of the objection and canceled the BPSK decision. The author concludes that Law no. 4 of 2023 in essence protects consumers in the field of E-Commerce where consumer protection is in E-Commerce In essence the P2SK Law and POJK PK facilitate the protection of consumer rights to obtain quality services in accordance with the principles of financial consumer protection OJK handles consumer complaints according to their respective authorities each of these matters has been stated in Article 245 of Law No. 4 of 2023. Based on the considerations of the panel of judges, the author is of the opinion that the Panel of Judges at the Garut District Court is appropriate in adjudicating the case based on the mandate of the Law. No.4 of 2004 concerning Judicial Power.